Algumas considerações sobre sintoma e linguagem na psicanálise - Pelenz, Maria Lúcia Fank (2021)
This work intends to delineate some articulations between the symptom and the language, according to the psychoanalytical framework. First, with Freud, we will take the symptom as a formation of the unconscious that is under the effect of the affect of anxiety and which has its meaning paired with desire and with the way the individual singularizes itself. Later, we will see, more precisely, how Lacan resumes this link between symptom and desire using the structure of language, more specifically, the laws of metaphor and metonymy, whose operation is homologous to what Freud, in his literal reading of the structure of dreams, called condensation and displacement. Finally, we will try to discuss that, beyond this signifying structure, the articulation between symptomatic repetitions and the inscription of a privileged signifier only acquires its value when considered in its jouissance dimension. In summary, by revisiting the foundations of psychoanalysis taking the symptom as the main issue, we intend to shed light on psychoanalytic theory and practice today.